1955
DOI: 10.1161/01.res.3.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antithrombin and Heparin Co-factor Activities of a Fraction Adsorbed from Plasma by Aluminum Hydroxide

Abstract: A chemical method has been devised for the quantitative determination of plasma antithrombin. A concentrate of antithrombin has been prepared from plasma. It also contains heparin cofactor activity. The two distinct activities could not be separated and may quite possibly be the properties of a single substance. When the concentrate is combined with heparin the capacity of the concentmte to destroy thrombin is not increitsed but there is interference with the thrombin fibrinogen interaction. In a mixture of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…The observation that thrombin splits the methylester linkage of p-toluensulphonyl-arginin-methylester (TAMe) (15) was first utilized in an At-III assay by Monkhouse et al (16) in 1955. TAMe has a relatively low thrombin suscepti bility, and was not well-suited for routine use.…”
Section: Assay Methods With Synthetic Substratesmentioning
confidence: 99%
“…The observation that thrombin splits the methylester linkage of p-toluensulphonyl-arginin-methylester (TAMe) (15) was first utilized in an At-III assay by Monkhouse et al (16) in 1955. TAMe has a relatively low thrombin suscepti bility, and was not well-suited for routine use.…”
Section: Assay Methods With Synthetic Substratesmentioning
confidence: 99%
“…[52][53][54] The recognition that heparin required a plasma cofactor for its full anticoagulant effect led to the identification of what was later called antithrombin III, and now just antithrombin. 50,55 The lysis of blood clots was recognized in antiquity, and in 1893 Dastre in France gave the term "fibrinolysis" to the effect of serum in lysing fibrin. 56 In 1933, Tillett and Garner in Baltimore identified a fibrinolysin in streptococcal lysates, and studies of the plasma cofactor required for this "streptokinase" activity led to its identification by Kaplan in North Carolina as plasminogen in 1944.…”
Section: Brief Histories Of Select Topics In Hematologymentioning
confidence: 99%
“…Work by several investigators in the 1950's [29,32,51] suggested the similarity of plasma antithrombin activity and plasma heparin cofactor activity. It was shown that heparin acted to accelerate the interaction between antithrombin and thrombin 50-100 fold.…”
Section: Intrinsic Coagulation Pathwaymentioning
confidence: 99%